Properties of Thrombolytic Agents in Vitro Using a Perfusion Circuit Attaining Shear Stress at Physiological Levels - Nishino, N; Scully, M F; Rampling, M W; Kakkar, V V (Thrombosis and Haemostasis, 1990)
A perfusion circuit was designed to investigate in vitro some of the factors which may influence the success of thrombolytic treatment in vivo. The rate of lysis of clotted plasma and different types of artificial thrombi (fibrin thrombi or whole blood thrombi) was measured in citrated plasma or whole blood under static conditions or under shear stress equivalent to the arterial or venous circulation. With both streptokinase (SK) and tissue-type plasminogen activator (t-PA) the rate of lysis of fibrin thrombi and whole blood thrombi was reduced significantly, when compared to the conventional plasma gel clot model (25-fold and 8fold, respectively). This occurred particularly with SK which showed a reduction (4-fold) in potency relative to t-PA under these conditions. Lysis of thrombi by both activators was observed to be faster in plasma than whole blood, and also faster with whole blood thrombi than fibrin thrombi. High shear stress, generally, caused a reduction in the rate of lysis of fibrin thrombi and an increase in the rate of lysis of whole blood thrombi compared to lysis rates under static conditions. Under all conditions of flow the lysis rate observed at 50 units t-PA per ml was much faster than that at 500 units per ml unlike the conventional plasma gel clot model.